Simulasi Aplikasi Pendeteksi Penggunaan Masker Muka Dalam Membantu Pengawasan Program 3M - Arnold Nasir (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
The Coronavirus has made severe damage to the society around the world. Every aspect of human life was affected. As the result, the government propose the “new normal” policy to be applied as the new standards for regulating people in doing their activities. One of the rules within the new normal policy is each people must wear a face mask when they are in a public space. In order to enforce the rule, the implementation of TensorFlow in a face detection technology becomes one of the solutions, especially in the university environment.